توجيهات الإمام الكرماني لمتشابه القرآن من خلال كتابه البرهان - دراسة تحليلية مقارنه للآيات من سورة آل عمران - نور اهدى مسعي أحمد (University of Eloued جامعة الوادي, 2024)
"هذه المذكرة تحت عنوان :(( توجيهات برهان الدين الكرماني في كتابه البرهان دراسة تحليلية مقارنة سورة ال عمران – انموذجا - )). تهدف هذه الدراسة إلى موضوع أساسي وهو : معرفة توجيهات الكرماني مقارنة مع أراء الجمهور من المفسرين فيما يخص المتشابه اللفظي . فقسمت دراستي هذه إلى شقين شق نظري وشق تطبيقي فالنظري تطرقت فيه إلى التعريف بصاحب كتاب البرهان والتعريف بالكتاب نفسه والموضوع الذي يعالجه . والشق التطبيقي قمت بدراسة نماذج من كتاب البرهان وكان المنهج المعتمد في هذا كله منهج وصفي تحليلي مقارن . وتوصلت في هذه الدراسة إلى معرفة المؤلف ومنهجه واراءه حول ايات المتشابه اللفظي ؛ فالإمام الكرماني يعد من أهم العلماء الذين الفوا في هذا العلم ويعد كتابه العمدة في بابه . "Title: The Guidelines of Burhan al-Din al-Karmani in his Book al-Burhan: An Analytical Comparative Study - Surat Al-Imran as a Model This study aims to investigate the guidelines of Burhan al-Din al-Karmani in his book Burhan compared to the opinions of the majority of al-ambiguity (mutashabih lizzi of verbal ambiguity I. interpreters regarding verbal The study was divided into two parts: theoretical and applied. The theoretical part included defining the author of al-Burhan, the book itself, and the topic it deals with. The applied part involved studying samples from al-Burhan using a descriptive, analytical, and comparative approach. The study concluded that Burhan al-Din al-Karmani is one of the most important scholars who wrote on this subject, and his book is considered a cornerstone in its field. The study also revealed the author's methodology and his opinions on the verses"
Keywords: الإمام الكرماني، متشابهة القرآن، كتاب البرهان; Imam Al-Kirmani; Similarities of the Qur’an; Book of Evidence